Eco tech investing in regenerative futures - Undheim, Trond Arne (Tantor Audio, 2025)
The book is a seminal contribution from a leading futurist who, over the past three decades, has explored each of the most disruptive forces shaping our world today. Eco Tech brings all this thinking together, fusing insight from thought leaders with the author's own considerable experience, to explore scenarios for 2050 and discuss eco-effectiveness as an established practice for governments, corporations, startups, and individuals. Trond Arne Undheim begins by providing a brief history of sustainability and provides simple definitions for key terms. Undheim also explores the ambitions of regeneration and offers a new conceptual framework to facilitate future discussion around sustainable innovation. He applies this framework to green, ambitious startups and examines the way these ventures will lead the way towards an eco-effective society. Finally, the book takes a deep dive into emerging eco-innovations. The book contains clear directions on how to progress through adversity and avoid returning to the status quo. The book will be an essential guide for executives, sustainability professionals, and energy tech investors who are concerned with the future and are prepared to both significantly invest in it and make behavioral changes. It will be a great resource for students and scholars of sustainable investing and innovation.
Audio book. - Online resource; title from title details screen (cloudLibrary, viewed March 12, 2025)
Keywords: Diffusion of innovations; Technological innovations -- Social aspects; Innovations; Diffusion; Innovations; Aspect social; Sustainable Development; Ecology; Life Sciences; SCIENCE; Global Warming & Climate Change; Development; BUSINESS & ECONOMICS; Audiobooks; Livres audio